Experimenting with Diffractive Analysis Practices While Walking-with River: Audiowalking and Micromapping - Vanessa Wintoneak (Australian Journal of Environmental Education)
This paper shares how a river-walking project in early childhood education created and experimented with two practices diffractively as an effort to do research differently. The year-long study, situated in Western Australia, explored river-child relations while walking with Derbarl Yerrigan/Swan River and was interested in decentring the human and attuning to more-than-human relations through situated practices. Using a feminist environmental framework this project took a non-representational approach to analysing data through two intra-related diffractive concepts: re-turning and re-membering. These concepts grounded the two practices, audiowalking and micromapping, and helped to shape the various forms of experimentation for a diffractive approach to analysis. Audiowalking is a practice that involved creating narrated audio recordings while walking with an intention of layering data from the present with pasts and futures. Micromapping is an embodied and performative practice that reimagined and unsettled place and space through mapping emotional encounters, river relations and the more-than-human. This paper shows how environmental education researchers, particularly those conducting place-based research, can approach research analysis diffractively to disrupt colonial ways of knowing, being and doing research through two practices that take a non-linear conceptualisation of time, embody data and research with worlds.